Evaluación técnica de un sistema de climatización bajo el reglamento RITE , para Acaire (2019)
"This project is carried out due to the lack of quality in buildings, whose purpose is to meet a thermal demand, either for air conditioning or water heating, and thanks to the technical regulation of thermal installations in buildings, hereinafter “RITE”, A technical evaluation is achieved. A building was defined to diagnose its current state, after the selection of the installation, key parameters were identified and critical points were determined, where measurements will be made. Finally characterize the building under study. With the data obtained from the characterization, the technical evaluation will be carried out, validating the previously established standards that will allow the diagnosis of the building, validating its compliance with the RITE and thus providing necessary recommendations for the building to be accredited with the RITE.